2012
DOI: 10.1103/physrevlett.109.017801
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-Stabilized Decorated Polar Liquid-Crystal Fibers

Abstract: Geometric frustration gives rise to new fundamental phenomena and is known to yield the formation of exotic states of matter, such as incommensurate crystals, modulated liquid-crystalline phases, and phases stabilized by defects. In this Letter, we present a detailed study of polar structure of freely suspended fluid filaments in a polarization modulated liquid-crystal phase. We show that a periodic pattern of polarization-splay stripes separated by defect boundaries and decorating smectic layers can stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
(86 reference statements)
2
14
0
Order By: Relevance
“…Labyrinthine structures reversibly disappear during the transition to the nonmodulated phase. This behavior is similar to that of freely suspended filaments formed in the polarization-modulated phase by the investigated material [33]. Furthermore, the instability onset appeared inside the SmC region and was not associated with a phase transition.…”
Section: Discussionsupporting
confidence: 77%
“…Labyrinthine structures reversibly disappear during the transition to the nonmodulated phase. This behavior is similar to that of freely suspended filaments formed in the polarization-modulated phase by the investigated material [33]. Furthermore, the instability onset appeared inside the SmC region and was not associated with a phase transition.…”
Section: Discussionsupporting
confidence: 77%
“…A theoretical model proposed by Saffman and Delbrück [25,26] and later extended by Hughes, Pailthorpe, and White [27] describes the Brownian diffusion of inclusions in thin membranes embedded in another medium, such as air. Recent experiments have verified these model predictions for the hydrodynamic behavior of micron-size inclusions in fluid smectic films [21][22][23]. There have been several reports on the self-organization of droplets and islands in smectic films [28][29][30] but there are few studies of the diffusion and aggregation of nanoparticles in these systems.…”
Section: Introductionmentioning
confidence: 69%
“…Liquid crystals, well known for their electrooptic properties and widespread application in displays, exhibit phases with varying degrees of orientational and positional order, making them attractive tools for controlling self-assembly at the nanoscale [19,20]. In addition, the promise of using freely-suspended films as a platform for modeling biological membranes provides a unique motivation for studying hydrodynamics in these essentially two-dimensional fluids [21][22][23]. The ability of smectic A liquid crystals to form inherently stable, thin membranes with quantized thickness has led to several experimental studies of the diffusion of inclusions in films.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Examples include the twist-bend nematic phase [3][4][5] characterised by ambidextrous heliconical structure on 10-nm range without layering; the helical nanofilament phase [6] of 30-40 nm wide stack of twisted layers with about 100 nm half pitch and the so-called B7 material [7,8] that forms peculiar micrometre scale helical patterns and slender freely suspended filaments. [9][10][11][12][13][14] The amazing optical B7 textures attracted an intense research that lead to many important findings. [7][8][9]13,[15][16][17][18][19][20][21] Small angle X-ray scattering (SAXS) [7,16,19] studies revealed a number peaks [16,19] that can be indexed by a slightly oblique monoclinic 2D unit cell with a~3-5 nm and b~8-20 nm periodicities.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] The amazing optical B7 textures attracted an intense research that lead to many important findings. [7][8][9]13,[15][16][17][18][19][20][21] Small angle X-ray scattering (SAXS) [7,16,19] studies revealed a number peaks [16,19] that can be indexed by a slightly oblique monoclinic 2D unit cell with a~3-5 nm and b~8-20 nm periodicities. This can be interpreted either as a columnar [19,21] or as an undulated smectic layer structure [16]; in the columnar model, the layers break into ribbons with half layer steps, whereas the undulated layers are continuous.…”
Section: Introductionmentioning
confidence: 99%